<svg xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg" style="vertical-align:-0.2631903pt" id="M1" height="8.60421pt" version="1.1" viewBox="-0.0657574 -8.34102 10.6147 8.60421" width="10.6147pt"><g transform="matrix(.018,0,0,-0.018,0,0)"><path id="g5-223" d="M563 442L553 454L479 439C463 404 440 354 416 322H414C389 422 344 454 283 454C151 454 21 310 21 162C21 48 73 -12 135 -12C182 -12 249 19 325 126H327C339 20 368 -12 407 -12C452 -12 507 21 557 110L530 136C508 107 493 92 480 92C462 92 453 123 430 253C459 292 528 386 563 442ZM318 186C290 133 235 76 202 76C175 76 154 108 154 184C154 275 198 406 247 406C288 406 313 294 318 186Z"/></g> MSH Blunts Endotoxin-Induced MuRF1 and Atrogin-1 Upregulation in Skeletal Muscle by Modulating NF-<svg xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg" style="vertical-align:-0.2631903pt" id="M2" height="8.60421pt" version="1.1" viewBox="-0.0657574 -8.34102 9.5915 8.60421" width="9.5915pt"><g transform="matrix(.018,0,0,-0.018,0,0)"><path id="g5-232" d="M506 405C506 432 483 454 457 454C408 454 367 413 305 342L196 211L228 373C232 393 235 410 235 418C235 442 225 454 206 454C172 454 102 416 21 346L38 316C67 337 93 353 103 353C106 353 110 342 103 311L31 -2L34 -12C73 -5 114 0 153 3L187 157C193 165 207 183 219 189L267 67C293 2 321 -12 349 -12S434 11 496 100L472 127C444 94 423 81 416 81C407 81 399 92 380 127C362 161 317 265 310 285C335 314 378 363 420 363C433 363 444 361 454 354C461 349 467 349 475 355C489 365 506 385 506 405Z"/></g> B and Akt/FoxO1 Pathway - Martín, Ana Isabel; Gómez-SanMiguel, Ana Belén; Gómez-Moreira, Carolina; Villanúa, María Ángeles; López-Calderón, Asunción (Mediators of Inflammation, 2014)
Alpha melanocyte stimulating hormone (αMSH) has been shown to have anti-inflammatory and anticachectic actions. We hypothesized that αMSH administration could attenuate the effect of lipopolysaccharide (LPS) on the skeletal muscle through modifications in IGF-Akt-FoxO1 pathway, or/and in serum corticosterone. Adult male Wistar rats were injected with LPS and/or αMSH. αMSH administration reduced LPS-induced increase in liver TNFα and serum nitrites as well as NF-κB activation in skeletal muscle. In contrast, αMSH was not able to prevent the stimulatory effect of LPS on serum concentration of ACTH and corticosterone. LPS decreased serum levels of IGF-I and IGFBP3 and their expression in the liver (P<0.01). However IGFBP3 expression in the gastrocnemius was increased by LPS. Treatment with αMSH prevented the effects of LPS on IGFBP3 but not on IGF-I. In the gastrocnemius αMSH blocked LPS-induced decrease in pAkt as well as the increase in pNF-κB(p65), FoxO1, atrogin-1, and MuRF1 levels. These results suggest that αMSH blunts skeletal muscle response to endotoxin by downregulating atrogenes and FoxO1 at least in part by controlling NF-κB activation and Akt signalling, but not through modifications in the secretion of corticosterone or IGF-I.